Identification of the bovine HSL gene expression profiles and its association with fatty acid composition and fat deposition traits. (September 2017) - Fang, Xibi; Zhao, Zhihui; Jiang, Ping; Yu, Haibin; Xiao, Hang; Yang, Runjun
Abstract: Hormone-sensitive lipase (HSL) is an intracellular neutral lipase capable of hydrolysing a variety of esters and is considered to be a candidate gene affecting fat deposition traits. Gene expression profiles of HSL were analysed in various adipose tissues of cattle, and the effect of HSL on lipid metabolism genes was analysed by a PCR array. Novel polymorphisms were identified within the HSL regulatory domain by sequencing, and the relationship between HSL variants and fat deposition traits was analysed. HSL mRNA was highly expressed in the subcutaneous and visceral fat of cattle. CPT1B/CPT1C and other lipocatabolic genes were upregulated, and lipogenesis-related genes ( FASN, LPL and ACOT12 ) were downregulated by HSL overexpression in BFFs. Five novel variants in the HSL functional domain were significantly associated with fat deposition traits, including FCR, LBT, MFW and fatty acid composition. HSL plays a pivotal role in the regulation of lipolysis and fatty acid biosynthesis in beef cattle.